Design and Analysis of Thinned Array Pattern Reconfigurable Antenna to Enlarge the Scanning Range - Zhangjing Wang; Xing Fan; Haijuan Cui; Shaoqiu Xiao (International Journal of Antennas and Propagation)
A novel thinned array with symmetric distribution along the array center is proposed in this paper. The proposed symmetric thinned array is based on the theory of unequally spaced array and the amplitude of each element in the array can be changed by introducing the weighted function. The pattern of the proposed array can be properly adjusted by changing the weighted function and the amplitude of the weighted factor, which obviously releases new degrees of freedom in array design. It has advantages such as low side lobe level (SLL) in the visible region, no grating lobes, and low nearby side lobe level (NSL), which has good potential for wide-angle scanning. Both simulation and experiment have been done; the experiment results show that, by applying this novel symmetric thinned array with pattern reconfigurable quasi-Yagi antenna, the scanning range of the array is −70°~70° in H-plane with SLL almost −10 dB below the maximum of the main beam. The 3 dB beam-width coverage is −86°~86°, which means that the proposed array can realize the entire upper-space beam coverage and restrain the SLL at the same time.